Awareness and Preventive Measure on Dengue Fever among Community People in Kathmandu - Adhikari, Jamuna; Oli, Sita; Pandey, Apsara; Dangol, Bhuwan Kumari (Journal of Advanced Academic Research, 2023)
Introduction: More than one-third of the worldwide populations are affected by dengue fever. It is a public health problem. The objective of this study is to find out the awareness and preventive measure on dengue fever. Method: A Descriptive Cross-sectional research design was adopted to collect the data from 346 people by non-probability purposive sampling technique. A semi-structured questioner was developed based on intensive literature reviewed. The investigator herself after the approval of the IRC (Institutional review committee) TUIOM collected data. Before data collection, formal permission was obtained from the ward office of Chandragiri municipality-5. Written consent was obtained from each individual sampling unit before interview and observation. The findings were described in descriptive statistics. Result: All most all (95.4%) respondents were heard about dengue fever. All respondents answered dengue can be prevention, but 40.17% respondents were known it is viral infection, 29.19% belief it is communicable diseases transmitted by mosquito (48%), but the specific types of mosquito (Aedes aegypti), known only 36.7% of respondents. Majority of respondents (84.39%) known it is transmitted by mosquito to human being and below half (47.68%) of respondents known this type of mosquito is breeding in clean stagnation water and bite in day and dusk 67.63%. All most all respondents known about signs and symptoms of the dengue high fever (98.84%), headache (74.85), body ache (62.71%), retro orbital pain (36%), easily bleeding (32.26%) flushing (26.58%), sore throat (23.12 %), skin erythema (16.18%), and photophobia (15.89%), are early signs of dengue infection. Sixty-three percent respondents know the vomiting is late signs of dengue infection, lethargy (43.35 %), blood disorder (35.54%), weakness (30.92%), shock (22.54 %), and bleeding (21.38%), are late signs of dengue infection. Only 46.82% respondents know management of dengue infection, Below half (44.8%) respondents’ answered its prognosis is good, majority of respondents known about complication of dengue is bleeding and shock and 19% respondents known vaccine is not availed of dengue infection till date. In mosquito controls measures, highest number of respondents (66.5%) were aware on environment sanitation can control the mosquito; all most all respondents were aware on mosquito control is the only one solution of the dengue control. Conclusion: The awareness regarding dengue in the study participants are not sufficient and preventive practices are not satisfactory. Improvement of prevention practices for dengue transmission must be emphasized.